THE INFLUENCE OF CREATIVE ACCOUNTING PRACTICES ON THE RISK OF TAX AUDITS BY THE DIRECTORATE GENERAL OF TAXES - Surya Anugrah; Windy Permata Suyono; Eka Septariana Puspa (Adisam Publisher, 2025)
This research aims to examine the influence of creative accounting practices on increasing the risk of tax audits by the Directorate General of Taxes (DJP) through a systematic literature review approach. Creative accounting, although not necessarily against the rules, is often used to embellish financial reports and aggressively reduce tax burdens. Practices such as manipulating revenue recognition, setting costs, using derivative instruments, and transfer pricing have the potential to give rise to suspicious financial indicators, such as unreasonable profit margins and significant differences between fiscal and commercial profits. DGT responded to this phenomenon by implementing a risk-based monitoring system, digitizing reporting, and utilizing third party data to increase the accuracy of inspection selection. The results of the study show that the more complex and aggressive the creative accounting practices used, the higher the possibility of taxpayers becoming the object of audit, so education and strengthening integrity in financial reporting and taxation is needed.